ANALGESIC PROPERTY OF PARALYTIC SHELLFISH TOXIN EXTRACTED FROM PERNA VIRIDIS (LINNAEUS, 1758) AND MERETRIX MERETRIX (LINNAEUS, 1758) - Sharma, Rupam; Venkateshvaran, K.; Purushothaman, C. S. (Journal of Indian Fisheries Association, 2011)
Paralytic Shellfish Toxin (PSP) in one of the potent neurotoxin accumulated in the filter-feeding bivalves without harming themselves. But when consumed as sea food diet; it causes intoxication to consumer. On the other hand, many bioactive compounds are being extracted from the plants and animals including the marine one which possess many biomedicinal properties like analgesic activity that can be used for the benefit of the human being. In this study, the PSP toxin extracted from Perna viridis and Meretrix meretrix, was assayed to see whether it possesses any analgesic activity. It was found that the crude extract exhibited little bit of analgesic property in comparison to the control but negligible in comparison with paracetamol. The pure extract or toxin may show better analgesic activity than the crude sample.Â Key words: Paralytic shellfish toxin, Analgesic activity, Perna viridis, Meretrix meretrix.